THE RELATIONSHIP BETWEEN ENVIRONMENT PERFORMANCE AND PROFITABILITY: A SECTORAL COMPARISON IN INDONESIA AND MALAYSIA - Ilyona Risty; Junika Halawa (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study investigates the impact of environmental performance on financial performance in Indonesia and Malaysia, focusing on sectors with diverse environmental practices. Using secondary data from publicly available company reports, the research explores whether better environmental performance correlates with higher financial outcomes, specifically Return on Assets (ROA). The analysis employs panel data regression, which reveals that environmental performance positively influences financial performance, with a statistically significant coefficient for environmental performance. However, the model's explanatory power is modest suggesting that while environmental efforts are beneficial, they only partially explain variations in financial performance. This research offers practical implications for business practitioners, policymakers, and investors, emphasizing the importance of integrating environmental performance into broader business strategies to achieve sustainable financial success. The study also calls for further research to investigate the mediating factors and industry-specific variations that could enhance the understanding of the environmental-financial performance nexus, particularly in developing economies. The results provide a foundation for future studies exploring the intersection of environmental sustainability and financial performance in diverse global contexts.